Innovative pathways for university entrepreneurship in the 21st century - Hoskinson, Sherry; Kuratko, Donald F. (Emerald, 2014)
The complex global environment for entrepreneurship has experienced significant change during the past decade. University based entrepreneurship is at the nexus of this environment. Students and faculty of entrepreneurship are uniquely positioned as agents in the movement of discovery and innovation.
Includes index.
Keywords: New business enterprises.; elektronické knihy; electronic books